Pyrylazo Dye: A Novel Azo Dye Structure with Photoinduced Proton Release and Highlighted Photophysical Properties in Biological Media - Santos, Willy G.; Pereira, Lucas H. [UNESP]; Ramin, Beatriz B. S. [UNESP]; Botelho, Sabrina M.; Morais, Sinara T. B.; Cardoso, Daniel R.; Santagneli, Silvia H. [UNESP]; Ferreira, Fabio F.; Leitão, Andrei; Ribeiro, Sidney J. L. [UNESP] (American Chemical Society (ACS), 2025)
A straightforward method for synthesizing a stable, photoreactive, and fluorescent-probe azo dye molecule is presented, highlighting the influence of azo and pyrylium groups within the electronic structure of the novel dye. This compound, named the pyrylazo molecule, is synthesized through the chemical reaction between 2,4,6-trimethylpyrylium and a 4-methoxybenzenediazonium species. The methyl group at the para position of the pyrylium readily reacts with the diazonium molecule, forming a stable protonated pyrylium-azo dye (N-protonated pyrylazo). The pyrylazo structure can easily change into its N-deprotonated form upon introduction of a weak base, such as an amine, promoting significant spectral shifts in the visible absorption and fluorescence bands. Because of that and other photochemical properties, this novel dye has shown significant potential for applications in photoinduced processes and biological contexts, particularly in Coulombic interactions with micelles and animal cells. In contrast to other nonfluorescent azo dyes, the singlet excited state of pyrylazo is deactivated through a radiative process in organized media, as evidenced by its behavior during micelle media, cell membrane permeation, and fluorescence emission in the cytoplasm. Nanosecond-transient absorption spectroscopy reveals a reversible photoinduced proton release process occurring in the excited singlet state, suggesting that the excited states of pyrylazo may play roles in transport through ion channels, artificial photosynthesis, and photoinduced protein folding. These promising applications underscore the pyrylium-azo structure as a novel dye with remarkable photochemical and photophysical properties not observed in other azo dye molecules reported before.